Real-time thermography system for composite welding: Undamaged baseline approach. (15th June 2021) - Flora, F.; Boccaccio, M.; Fierro, G.P.M.; Meo, M.
Abstract: The aerospace industry's current focus on recyclable materials and low-cost processes has accelerated research and implementation of thermoplastics matrix composites (TPC). In the last decades, researchers have researched weldability of these materials as a valid alternative to conventional mechanical fastening and adhesives, for improving the strength of the joint. Automatic induction welding of carbon fiber TPCs is one of the most promising techniques due to its numerous benefits, such as elevated energy efficiency and highly localised heat. As for all the manufacturing techniques, the importance of efficiently detecting the presence of defects during TPCs welding has pushed the need for automated real-time non-destructive evaluation (NDE) systems. This paper focuses on the development of an efficient NDE technique able to detect the presence of alterations and defects in real-time during the welding process. This technique relies on Infrared (IR) active thermography inspections performed using the induction welding heat as the source and an undamaged baseline methodology to detect differences in the heat field. The procedure was experimentally analysed by means of an apparatus capable of automatic welding of samples, performing the real-time NDE during the process. Results show the efficiency of the method to localise the damaged area and characterise the defects during the welding. The undamaged baseline methodology was proven to better clarify shape and location of defects, allowing for an efficient detection of damaged samples and areas where more detailed inspections can be performed after the welding process by means of the same IR apparatus.